Effect of Growth Hormone (GH) and Resistance Training on the Collagen Properties of Femoral Bone Tissue - Castoldi, Robson Chacon [UNESP]; Manganaro, Lincoln Jose; Ferreira, Soraia Carolline; Alves, Marcelo Jose; De Carvalho Filho, Carlos Augusto; Garcia, Thiago Alves; Tamura Ozaki, Guilherme Akio; Santos Caetano, Heliard Rodrigues dos; Carvalho Zanuto, Everton Alex; Giometti, Ines Cristina; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Chilena Anatomia, 2019)
The indiscriminate use of anabolic steroids in gyms has been growing in a generalized way, among which, the most common is growth hormone (GH). In the short term GH may potentiate muscle growth, especially when taken in combination with resistance training. However, the effects of this hormone are not yet fully understood in the literature, especially in relation to collagen properties. The objective of this study was to evaluate the effect of the application of growth hormone (GH) and resistance training (RT) on the collagen properties of femoral bone tissue using Raman Spectroscopy. In this study 40 male rats were randomly distributed into four groups (n=10): control (C), control and GH application (GH), resistance training (T), and resistance training and GH application (GHT). The training consisted of four series of 10 water jumps, performed three times a week, with an overload corresponding to 50 % of body weight and duration of four weeks. GH was applied at a dosage of 0.2 IU/Kg (0.067 mg/kg) to each animal, three times a week, every other day. The animals were euthanized and the right femurs were collected for analysis of bone structure. Raman spectroscopy (RS) was used to observe the following compounds from their respective bands: type I collagen (662 cm(-1)), amide III (1243 cm(-1)), proteins including type I collagen (1278 cm(-1)), woven collagen (1322 cm(-1)), association of collagen, phospholipids, nucleic acid, and phosphate (1330 cm(-1)), and collagen and protein deformation (1448 cm(-1)). The results demonstrated an increase in the collagen properties in all analyzed variables, however, the T group presented a statistically significant difference (p<0.05). It is possible to conclude that isolated physical training was shown to be more efficient than when combined with the application of GH to increase the collagen properties of the femoral bone tissue.
Keywords: Physical training; Growth hormone; Bone; Femur; Rats; Collagen